Zavarovalništvo kot pomembna gospodarska panoga - Krumberger, Maja (Podjetje in delo, 2015)
Insurance industry influences individuals, businesses and society. It is a vital part of society that promotes security, financial and economic stability, and growth of welfare. The article seeks to highlight the status and importance of insurance throughout the history. It explains the role insurance industry has in relation to individuals and to the society. Its role exceeds conclusion of an insurance policy; in its role as financial intermediary insurance represents the most efficient way of risk transfer for individuals, businesses, and the society. To understand insurance it is necessary to understand the business model that facilitates risk transfer. Insurance promotes knowledge in a way that helps individuals and the society to mitigate its risks. It promotes long-term prosperity, of which a micro insurance with the aim to diminish poverty around the globe is a good example. And above all, insurance plays a vital role in social security.
Keywords: finančno pravo; gospodarske dejavnosti; poslovno tveganje; zavarovalnice; zavarovalstvo